PETROLOGI BATUAN MAGMATIS NEOGEN DAERAH PANGKALAN KOTABARU LIMAPULUH KOTA SUMATERA BARAT - Bhakti H.Harahap (Jurnal Geologi dan Sumberdaya Mineral, 2007)
Neogene magmatic product in Pangkalan Kotabaru region are plotted by using TAS diagram (total alkali versus silica), and they have wide variations of rocks namely basaltic trachy andesite, basaltic andesite and dacite. On diagram SiO2 versus K2O, most of the Neogene andesite and dacite are classified as high-K calc-alkaline and rare normal calc- 2 alkaline and tholeiite, and on AFM diagram the samples are concentrated around the dividing line between calcalkaline and tholeiitic fields. In general, the Neogene volcanic rocks from this area are characterized by high aluminium (Al2O3) that varies from 15.50 - 18 wt%, low MgO (2-5 wt%), alkali (Na2O+K2O) content less than 8 wt% and low TiO2 (<1 wt%). While the trace element of the rocks is summarized on the spider diagram. Here their patterns are showing enrichment in large ion lithophile elements (LILE) and light rare earth elements (LREE) relative to high field strength elements (HFSE) and heavy REE (HREE). Moreover, these patterns show an Nb negative anomaly that resembles the typical characteristic of arc volcanism. The geochemical characteristic of the volcanic rocks from this area have lower concentrations of Ba, Sr and La than other active continental margins like the Andes volcanic rocks. Like many other subduction related rocks, this volcanism characterizes a very evolved magma with MgO contents ranging from 1-5wt% and low Mg# (MgO/MgO+FeOtotal) at maximum of 40. The island of Sumatera is on the western side of the Sunda Craton (Sundaland) where India-Australia Oceanic Plate is being obliquely subducted beneath the island since Eocene. The Neogene volcanic rocks from Pangkalan Kotabaru region have been interpreted to be directly related to this subduction process.Â Key words: magmatism, geology, Pangkalan Kotabaru, petrology, Neogene